Characterization of hepatitis B virus infection and viral DNA integration in non‐Hodgkin lymphoma. Issue 8 (9th May 2020) - Li, Mengge; Shen, Yuling; Chen, Yiming; Gao, Haifeng; Zhou, Jiaqin; Wang, Qing; Fan, Chunsun; Zhang, Wei; Li, Jin; Cong, Hui; Gu, Jinyang; Gan, Yu; et al.
Abstract: Hepatitis B virus (HBV) infection has been reported to be associated with non‐Hodgkin lymphoma (NHL). However, the evidence is limited to the seroepidemiological study. There is a lack of evidence showing the HBV infection and integration in NHL cells. Here, we reported that in the Shanghai area, the positive rates of serum HBsAg (OR: 3.11; 95% CI: 2.20‐4.41) and HBeAg (OR: 3.99; 95% CI: 1.73‐9.91) were significantly higher in patients with NHL. HBsAg, HBcAg and HBV DNA were detected in 34.4%, 45.2% and 47.0% of the NHL tissues, respectively. Furthermore, by using a high‐throughput viral integration detection approach (HIVID), integrated HBV DNA was identified from 50% (6/12) HBV‐related NHL tissues. There were a total of 313 HBV integration sites isolated from the NHL tissues, among which four protein‐coding genes ( FAT2, SETX, ITGA10 and CD63 ) were interrupted by HBV DNA in their exons. Seven HBV preferential target genes ( ANKS1B, HDAC4, EGFLAM, MAN1C1, XKR6, ZBTB38 and CCDC91 ) showed significantly altered expression levels in NHL, suggesting a potential role of these genes in NHL development. Taken together, HBV integration is a common phenomenon in NHL. This finding opens up a new direction of research into the mechanistic link between HBV infection and NHL. Abstract : What's new? Increasing sero‐epidemiological evidence has suggested a significant association between chronic hepatitis B virus (HBV) infection and non‐Hodgkin lymphoma (NHL). However, whether HBV infects NHL cells is still debated. Here, using a serological, histological, and genetic approach, the authors show that HBV integration is a common phenomenon in NHL. Expression analysis of the HBV preferential target genes identified seven novel candidate genes, which may have potential functions in NHL development. Taken together, the results provide direct evidence that HBV infection is an etiological factor of NHL. The information on HBV integration breakpoints provides new clues for mechanistic investigation of HBV‐induced NHL.